PENGARUH KOMPETENSI GURU TERHADAP KINERJA GURU DI SMA NEGERI 7 KABUPATEN TEBO - Pratiwi Indah Sari, Feby Anggraini, (Universitas Batanghari Jambi, 2018)
This study aims to determine the description of respondents and the influence of teacher competence on teacher performance in SMA Negeri 7 Kabupaten Tebo. Based on data analysis on the results of research that there is a significant influence between teacher competence on teacher performance in SMA Negeri 7 Kabupaten Tebo. With the result of model summary R = 0,505 and R Square = 0,342. In coefficient, the value of t = 9,258 with α (sig) = 0,006. Because α (Sig) <0,05, regression can be used to predict teacher competence at 95% confidence level. In coefficient the value of B constant = 70,599, states that if the teacher competence variable is ignored, then the teacher's performance = 70,599. Meanwhile, the variable value for teacher competence (X) is 1,210 stating that if the teacher's competency level is included, the teacher's performance increases around 1.210.Keyword : Teacher Competencies, Teacher Performance.